SOCIAL CAPITAL MANAGEMENT IN IMPROVING COMMUNITY WELFARE (CASE STUDY OF BAALUL MAAL HIDAYATULLAH SURABAYA) - Nur Halimah; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aimed to describe and analyze the role of social capital, as seen from the interrelation of networks, norms, and beliefs in improving the welfare of the community under the indicators of Maqashid Syariah. This study employed a qualitative approach with a case study strategy. Besides, this study has an analysis unit in the form of social capital and improvement of the welfare of the community who received scholarship assistance from Baitul Maal Hidayatullah of Surabaya. Also, data collection was carried out by interview and direct observation of the research object. The analysis technique utilized in this study was an explanatory analysis technique by explaining the results of interviews and direct observation. The study results reveal that social capital with norms, networks, and trust indicators play a role in improving the welfare of the community seen from the aspects of Maqashid Syariah.Keywords: Social capital, Welfare, and Maqashid SyariahREFFERENCE Al-Faizin, Abdul Wahid dan Nashr Akbar. (2010). Tafsir ekonomi kontemporer kajian tafsir al-qur’an tentang ekonomi Islam. Jakarta: Madani Publishing House.Amalia, Euis. (2009). Keadilan distributif dalam ekonomi Islam penguatan peran LKM dan UKM di Indonesia. Jakarta: PT. RajaGrafindo Persada.Chapra, Umer. (2001). Masa depan ilmu ekonomi (sebuah tinjauan Islam. Jakarta: Gema Insani Press.Field, John. (2010). Modal sosial. Bantul: Kreasi Wacana.Widayani, Retno dan Nisa Agistiani Rachman. (2003). Studi kemunculan modal sosial.Jurnal Kebijakan dan Administrasi Publik, 17(2), 1-75Yin, Rober K. (2010). Studi kasus design & metode. Jakarta: Raja Grafindo Persada.